Deconstructing gender: evidence on how programmes address gender inequalities to improve health. Issue 2 (17th February 2017) - Rottach, Elisabeth; Pappa, Sara; Dayal, Radhika; Das, Madhumita
ABSTRACT: A growing body of evidence demonstrates that incorporating approaches to address gender inequality in programmes can lead to improved health outcomes. This article aims to deconstruct the various dimensions of gender and identify how programmes address these domains to improve health. This study draws on a broader systematic review examining the impact of gender-integrated programmes on health outcomes in low- and middle-income countries. We identified 68 programmes meeting our criteria for inclusion. Our analysis found considerable variation in gender domains addressed across programmes, suggesting that more evidence is needed to understand the pathways through which gender-integrated programmes influence health.